Production of lipids by Chaetoceros affinis in media based on palm oil mill effluent - Karthick Murugan, Palanisamy; Primilla, Paramasivam; Gaanty Pragas, Maniam; Mohd Hasbi, Ab. Rahim; Natanamurugaraj, Govindan; Chisti, Yusuf (Elsevier B.V., 2021)
Biomass and lipid production by the marine diatom Chaetoceros affinis were characterized under continuous light with aeration. Media based on palm oil mill effluent (POME; 10, 20 and 30 % v/v in distilled water) were used together with a standard control medium. The maximum biomass concentration on day 12 of batch cultures in control medium was 821 ± 71 mg L–1. Under identical conditions, in the best POME medium (20 % POME v/v in distilled water with other inorganic components), the biomass concentration was reduced by ∼11 % to 734 ± 66 mg L–1. The lipid content of the biomass grown in the control medium was 50.8 ± 4.5 % by dry weight, but was a little lower (48.9 ± 4.1 % by dry wt) in the above specified best POME medium. In the best POME medium, oleic acid was the major fatty acid (72.3 ± 5.2 % by weight) in the total lipids extracted from the biomass and monounsaturated fatty acids were the main type of fatty acids (74.6 ± 5.2 %). POME levels of >20 % in the medium suppressed both biomass and lipid production relative to the medium with 20 % POME.